1998
DOI: 10.1021/la980084d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Behavior of Several Cobalt Porphyrins as Electrocatalysts for the Reduction of O2 at Graphite Electrodes

Abstract: Four cobalt porphyrins were adsorbed on graphite electrodes and used to catalyze the electroreduction of O2. The two porphyrins without substituent groups in the meso positions of the porphyrin ring operated at the most positive potentials and catalyzed the reduction of O2 to both H2O2 and H2O, but the H2O did not result from significant reduction of H2O2. The porphyrins containing meso substituents catalyzed only the reduction of O2 to H2O2. The catalysts that accomplish the four-electron reduction of O2 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
165
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 17 publications
14
165
1
6
Order By: Relevance
“…Moreover, the Dedicated to Professor Jose Zagal on occasion of his 65th birthday. cobalt porphine, protoporphyrin IX and 5,10,15,20-tetramethylporphyrin, were successfully employed to drive efficiently the reduction of oxygen [5,11]. Some reports postulated high catalytic activity of face-to-face porphyrins toward the oxygen reduction reaction to water [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Dedicated to Professor Jose Zagal on occasion of his 65th birthday. cobalt porphine, protoporphyrin IX and 5,10,15,20-tetramethylporphyrin, were successfully employed to drive efficiently the reduction of oxygen [5,11]. Some reports postulated high catalytic activity of face-to-face porphyrins toward the oxygen reduction reaction to water [12].…”
Section: Introductionmentioning
confidence: 99%
“…bimetallic, heme/Cu catalytic site in cytochrome c oxidase [1,2]. Their synthetic analogues have been used to activate molecular oxygen for the O 2 reduction to hydrogen peroxide (H 2 O 2 ) and/or to water in the solution [3], at the solid electrodes [4], or at the polarized liquid-liquid interfaces [5,6]. The activation process involves the binding of O 2 to the metal center, and the electron delocalization from the metal to O 2 , which can be viewed like a coordinated superoxide or peroxide anion, i.e., as a Brønsted base [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for catalysis comes from ion transfer voltammetry at the water|DCE interface using acidified Li 2 SO 4 and bis(triphenylphosphoranylidene)ammonium tetrakis(4-chloro-phenyl)borate (BTPPATPBCl) as the supporting electrolytes in water and DCE, respectively. Both water and DCE solutions were saturated with air and contained 0.25 mM O 2 [7] and 1.39 mM O 2 [8], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…124 Outstanding research in this area has been carried out by Anson and co-workers along the last twenty years. [125][126][127] Collman and co-workers [128][129][130][131] have shown that the simultaneous interaction of the O 2 molecule with two CoP centers is involved in the activation by a cofacial biscobaltporphyrin. However, more recently, they found out that the change of the electrode material from pyrolytic graphite to gold can switch the mechanism from tetraelec- 6,2003 tronic to bielectronic.…”
Section: Multielectron Transfer Catalysis By Supramolecular Films Of mentioning
confidence: 99%